2016
DOI: 10.1177/1063426616681980
|View full text |Cite
|
Sign up to set email alerts
|

Elementary and Middle School Teachers’ Self-Reported Use of Positive Behavioral Supports for Children With ADHD: A National Survey

Abstract: This study examined elementary and middle school teachers’ self-reported use of behavioral supports for students with attention-deficit/hyperactivity disorder (ADHD) from a national sample of teachers. This information is important given increased attention and emphasis on universal and targeted strategies within problem-solving models in schools. Participants were teachers surveyed from 26 states across North America about their use of behavioral supports for their students with ADHD. Results are grouped by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
3
16
0
Order By: Relevance
“…In-service teachers report that they use behavior modifications (i.e., consequence-based CMSs) and environmental and assignment modifications (i.e., types of antecedent-based CMSs) more frequently for inattentive students than for behavior-typical students (Murray et al 2011). This finding is in accordance with other studies showing that teachers indicate that they apply a wide range of CMSs to students with ADHD (Arcia et al 2000;Blotnicky-Gallant et al 2015;Hart et al 2017;Martinussen et al 2011;Mulligan 2001). Nevertheless, DuPaul et al (2018) found that fewer than two-thirds of students with ADHD currently receive educational support (i.e., school-based educational support, intervention, or accommodation, such as tutoring, extra help from a teacher, preferential seating, extra time to complete work, or being enrolled in special education), and only about one-third of students with ADHD receive classroom management (e.g., reward systems, behavioral modifications, or a daily report card).…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…In-service teachers report that they use behavior modifications (i.e., consequence-based CMSs) and environmental and assignment modifications (i.e., types of antecedent-based CMSs) more frequently for inattentive students than for behavior-typical students (Murray et al 2011). This finding is in accordance with other studies showing that teachers indicate that they apply a wide range of CMSs to students with ADHD (Arcia et al 2000;Blotnicky-Gallant et al 2015;Hart et al 2017;Martinussen et al 2011;Mulligan 2001). Nevertheless, DuPaul et al (2018) found that fewer than two-thirds of students with ADHD currently receive educational support (i.e., school-based educational support, intervention, or accommodation, such as tutoring, extra help from a teacher, preferential seating, extra time to complete work, or being enrolled in special education), and only about one-third of students with ADHD receive classroom management (e.g., reward systems, behavioral modifications, or a daily report card).…”
Section: Introductionsupporting
confidence: 88%
“…Furthermore, these authors demonstrated that general education teachers with moderate to extensive training in managing ADHD indicate that they use CMSs more frequently than those with no or only brief training. Hart et al (2017), by contrast, found that teachers' reported use of CMSs for students with ADHD is not related to teachers' years of experience and training in ADHD. There is evidence that teachers with more knowledge of ADHD are more prepared to seek professional services and to perceive treatment, including changes within the classroom, as beneficial (Ohan et al 2008).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations